TEI, the Walt Whitman Archive, and the Test of Time - Brett Barney (OpenEdition, 2021)
“Diachronic Markup and Presentation Practices for Text Editions in Digital Environments,” a 2014–15 transatlantic collaboration funded jointly by DFG and NEH, provided an occasion to test TEI’s relatively new provisions for encoding temporality. My experiences in attempting to apply these provisions to Walt Whitman manuscripts led me to conclude that chapter 11 of the TEI Guidelines should be significantly revised and that the basic dichotomy it introduces between <sourceDoc> and <text> deserves renewed scrutiny. Some of the problems in the chapter can be traced to the way the Guidelines have evolved over time through a series of choices motivated by expediency. The Whitman Archive has, since its first foray into TEI markup in 2000, been anxious to find a way to leverage its potential to encode the temporal characteristics and relationships among various manuscript and print instances. The customization we created, however, has shown itself inadequate to describe and make processable important genetic information. Unfortunately, TEI also continues to provide inadequate guidance in the area of encoding genetic relationships, both between documents and within them. My experiments during the Diachronic Markup project included using <listChange> to encode the sequence in which the text of a single document was inscribed and show that, although the Guidelines need to be developed with specific advice and examples, existing elements and attributes can be used to posit claims about the “way the page was filled,” thereby enabling useful processing and display.